A review of the Asian species of the genus Pachysternum (Coleoptera: Hydrophilidae: Sphaeridiinae) - Fikáček, Martin; Jia, Fenglong; Prokin, Alexander (Zootaxa, 2012)
The Asian species of the genus Pachysternum Motschulsky, 1863 are revised and redescribed. Three new species are de-scribed: Pachysternum kubani sp. nov. (Laos, China: Sichuan), P. rugosum sp. nov. (China: Gansu, Shaanxi) and P. san-dacanum sp. nov. (Malaysia: Sabah, Sarawak). Three new synonyms are established: Megasternum gibbulumMotschulsky, 1866 and Pachysternum sibiricum Kuwert, 1890 are junior synonyms of Pachysternum haemorrhoumMotschulsky, 1866; Pachysternum nigritum Jia, Wu & Pu, 1998 is a junior synonym of P. stevensi Orchymont, 1926.Pachysternum keralense Hebauer, 2002 is transferred to the pilocnemoides group of the genus Australocyon Hansen,1990. Megasternum japonicum Shatrovskiy, 1989 is resurrected from the synonymy with M. gibbulum and considered asa valid name. Lectotypes are designated for the following species: Pachysternum apicatum Motschulsky, 1863, P. curva-tum Orchymont, 1925, P. haemorrhoum Motschulsky, 1866, P. nigrovittatum Motschulsky, 1863, P. sibiricum Kuwert,1890, Megasternum gibbulum Motschulsky, 1866 and M. distinctum Sharp, 1873. All Pachysternum species are diag-nosed, relevant morphological characters are illustrated, and an updated identification key is provided. Pachysternum api-catum is interpreted as a polymorphic species exhibiting high geography-based variation and possibly consisting of somesibling taxa; diagnosing of these taxa requires more material and additional (ideally molecular) characters and is therefore left unresolved at the present time.